2021
DOI: 10.1017/s0022029921000650
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metabolic, oxidative and inflammatory status of Simmental × Holstein crossbred with parental breeds during the peripartal and early lactation periods

Abstract: The aim of the research reported in this paper was to evaluate plasma concentrations of energy, oxidative and inflammatory biomarkers of Simmental (sire) × Holstein (dam) crossbred cows, in comparison with the two parental breeds during the peripartal and early lactation periods and to estimate the effects of heterosis for these traits. Thirty-three animals, managed under the same conditions, 8 Simmental (SI), 9 Holstein (HO) and 16 crossbred (CR) cows were enrolled in this study. Glucose, non-esterified fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
2
2
0
1
Order By: Relevance
“…These results suggest that after stimulation with LPS, Brahman cattle had higher levels of oxidative stress than Brahman × Thai native crossbreed cattle. Our findings are consistent with those of De Matteis et al [31], who reported that oxidative stress levels were lower in Simmental × Holstein crossbreed cattle than in pure breed parents. Gonzalez-Añover et al [32] found that plasma H 2 O 2 concentrations were lower in lean hybrid pigs than in purebred Iberian pigs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that after stimulation with LPS, Brahman cattle had higher levels of oxidative stress than Brahman × Thai native crossbreed cattle. Our findings are consistent with those of De Matteis et al [31], who reported that oxidative stress levels were lower in Simmental × Holstein crossbreed cattle than in pure breed parents. Gonzalez-Añover et al [32] found that plasma H 2 O 2 concentrations were lower in lean hybrid pigs than in purebred Iberian pigs.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with those of De Matteis et al . [ 31 ], who reported that oxidative stress levels were lower in Simmental × Holstein crossbreed cattle than in pure breed parents. Gonzalez-Añover et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, n3 fatty acid, which has an antioxidant effect, plays an important role in the immunity of newborn calves (42,52). In parallel with the results of the present study, studies show that the survival rate of Holstein's calves is higher than that of Simmental calves (8,18). Also, higher levels of n3 in the milk are the desired factor for the higher quality of milk for consumption (27).…”
Section: Resultssupporting
confidence: 85%
“…В целом, IL8 считается мощным медиатором воспаления, а также участвует в привлечении лейкоцитов к местам инфекции (73). В связи с развитием мастита изучаются полиморфизмы гена IL8 (74,75). При этом сообщалось, что один из полиморфизмов -+472 A>G в IL8 связан с высоким числом соматических клеток в молоке коров, инфицированных S. aureus (76) Поскольку активность трипсина в крови связана с содержанием метаболитов оксида азота (77), есть вероятность участия трипсина в воспалительной реакции в ткани молочной железы.…”
Section: активность трипсина в молоке коров повышается при маститах о...unclassified